A picture paints a thousand words: Heart drawings reflect acute distress and illness perception and predict posttraumatic stress symptoms after acute myocardial infarction. Issue 1 (27th June 2015) - Princip, Mary; Koemeda, Miriam; Meister, Rebecca E; Barth, Jürgen; Schnyder, Ulrich; Znoj, Hansjörg; Schmid, Jean-Paul; von Känel, Roland
The aim of this study was to examine whether heart drawings of patients with acute myocardial infarction reflect acute distress symptoms and negative illness beliefs and predict posttraumatic stress symptoms 3 months post-myocardial infarction. In total, 84 patients aged over 18 years drew pictures of their heart. The larger the area drawn as damaged, the greater were the levels of acute distress ( r  = 0.36; p  < 0.05), negative illness perceptions ( r  = 0.42, p  < 0.05), and posttraumatic stress symptoms ( r  = 0.54, p  < 0.01). Pain drawings may offer a tool to identify maladaptive cognitions and thus patients at risk of posttraumatic stress disorder.